Escritas negras: oralitura, falatório e escrita performática à margem a partir de Stella do Patrocínio e Lindolfo Roberto Nascimento - Nascimento, Lindolfo Roberto (2024)
This dissertation establishes a critical reflection on black writings, in its relationships between art, raciality and black lives on the margins, from a communicational-poetic standpoint. Black writings are understood as writings on the margins, writings made with the body, found both in conceptions of literature and oraliture (Leda Maria Martins) and in language procedures such as falatório [blabbing] (Stela do Patrocínio) and performative writing (Lindolfo Roberto Nascimento). The work aims to analyze these black writings conducted, in particular, in situations of psychiatrization by means of performative procedures in the production of bodies, oralities and literary discourses on the margins, considered in their contaminations. Produced by black people, from Afro-diasporic origins, black writings comprise the research corpus, formed by the selection of the following literary works: Reino dos bichos e dos animais é o meu nome [Kingdom of the beasts and animals is my name] (2001), by Stela do Patrocínio—mediated by the publication edited by Viviane Mosé—and the so-called Experimento MAMEMI, by Lindolfo Roberto Nascimento—composed of the works Mandala naïf (2020), Medusa em braile [Medusa in Braille] (2021) and Miragens concretas [Concrete mirages] (2023). The intention is to identify the communicational procedures established in the two poetic conceptions in the constitution of silenced voices as denied subjectivities, observing how black writings, although constituted as artistic practices on the social margins, are no less important in understanding the contemporary artistic production. In this sense, the main problematization concerns questioning what determines black writings as writings on the margins. It means talking about black lives constituted by the poetic conception of the two authors in question. To this end, the theoretical foundation lies, in addition to Martins (black culture, oraliture and performance), in bell hooks (concepts of raciality and margin) and Christine Mello (for analysis of the corpus through the extremities approach). Drawing from bell hooks, the dimension of margin in the black writings of Patrocínio and Nascimento are related to the contaminations between oraliture, falatório [blabbing] and performative writing, thus resulting in the present notion of writings on the margin. We can see, in these black lives, bodies and oralities, the poetic dimensions of both vulnerability and resistance, which allows us to observe the re-signification of artistic practices in contemporaneity as the gesture of amplitude for contemporary writing made by non-minority minorities, agencies of society in their fight to reduce inequality